PENGARUH PENGALAMAN POLA ASUH OTORITER TERHADAP PENERAPAN POLA ASUH ANAK USIA 0-5 TAHUN KELOMPOK PKH DI WILAYAH KERJA PUSKESMAS PASIR PANJANG, KELURAHAN PASIR PANJANG - Agustina Ina; Yustinus Rindu; Yane Leo Mangi; Oklan Liu Nokas; Ina Debora Ratu Ludji (Jurnal Cakrawala Ilmiah, 2023)
Background: People with a weak economy tend to apply poor parenting. PKH families are recipients of social assistance registered in the Integrated Social Welfare Data (DTKS). This assistance is given to poor and vulnerable poor families with requirements. Objectives: This study aims to determine the effect of authoritarian parenting experience on the application of parenting to children aged 0-5 years of the PKH group in the Pasir Panjang Village area. Methods: This type of research is analytic with a cross sectional design... Sample: the sample in this study was obtained using purposive sampling technique totaling 52 respondents. Data collection was carried out using a questionnaire filled out by respondents. Results: the results of the multiple logistic regression test obtained a p value of 0.000. Conclusion: There is a significant relationship between the experience of authoritarian parenting and the application of parenting for children aged 0-5 years in the Pasir Panjang Health Center Working Area, Pasir Panjang Village, Kupang City